Development of Interactive Learning Videos on Grade IX Spatial Structure Material - Eka Titik Susiani; Olief Ilmandira Ratu Farisi (Journal of Creative Power and Ambition (JCPA), 2026)
Mathematics instruction on three-dimensional shapes in ninth-grade junior high school is still dominated by conventional media, such as textbooks, worksheets, and static teacher explanations. As a result, students often struggle to understand abstract concepts, including nets, surface area, and the volume of three-dimensional shapes. Therefore, learning media are needed that can present the material in a more engaging, interactive, and accessible manner through Android devices. This study aims to develop interactive Android-based educational video media for teaching solid geometry to ninth-grade students. The study employed a research and development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media were validated by media experts and subject-matter experts and evaluated through user feedback questionnaires. The data were analyzed using quantitative descriptive methods based on a Likert scale. The results showed that the developed instructional media received feasibility scores of 87.5% from media experts, 91% from subject-matter experts, and 91% from users. All evaluation results were classified as highly valid, indicating that the media have an attractive interface, are easy to use, and present content that is aligned with the learning objectives. Based on these findings, the developed interactive educational video media are considered suitable for use as a supplementary learning tool for teaching three-dimensional shapes to ninth-grade junior high school students.